PEMBERIAN EKSTRAK DAUN SIRSAK (Annona muricuta) UNTUK MEMPERBAIKI KERUSAKAN SEL BETA PANKREAS MELALUI PENURUNAN KADAR GLUKOSA DARAH, ADVANCED GLYCATION AND PRODUCT DAN 8-HIDROKSI-2-DIOKSIGUANOSIN PADA TIKUS WISTAR HIPERGLIKEMIA - Adhi Suastuti, Ni G. A. M. Dwi; Panca Dewi, I G. A. Kunti Sri; Ariati, Ni Komang (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015DO - 10.24843/JCHEM.2015.v09.i02.p21, 2015)
This research aimed to determine the effectivity of soursop leaf extract to repair beta pancreatic cells damaged in Wistar rats induced by alloxan. This experiment used randomized posttest-only control group design . In this experiment, 24 Wistar rats were used which divided into four groups, control group (K), and three treatment groups (P). P1 was the group tretment with a dose of 50 mg/kg bw/day, P2 with a dose of 100 mg/kg bw/day,  and P3 was the group treatment with a dose of 150 mg/kg bw/day extract. All groups were induced by alloxan with a dose of 150 mg/kg bw to obtain condition of hyperglycemia. The results showed that blood glucose levels decreased after treatment with the extracts. Glucose levels in group K, P1, P2, and P3 were 208.0 mg/dL; 177.5mg/dL; 164.7 mg/L and 137.0 mg/dL respectively. After 2 weeks of treatment, the level of 8-OHdG and AGEs were also reduced. The lowest level was observed in P3 treatment which the level of 8-OHdG 1.664ng.mL and 0.033 mol/L for AGEs level. In conclusion the soursop leaf ( Annona muricata) extract given at a dose of 150 mg/kg bw/day can improve beta pancreatic cells resulted from antioxidant activity content in the extract which function as antihyperglycemia. Based on GC-MS spectra analysis,  the the soursop leaf ( Annona muricata) extract consisted of caryophyllene, ethyl tetradekanoat, acid 2-cyclohexane-1-one, 4-hydroxy-3,5,6-trimethyl-4-(3-oxo-1-butenyl), hexa ethyl decanoate , phytol, thiazole-2,4 (3H, 5H) _dion, 5 benzilideno-3 [etifenilamino) metal], 9-octadecanoic acid, ethyl linoteat, ethyl oleate and ethyl octadecanoic.
Keywords: Soursop leaf, blood glucose levels, hyperglycemia, AGEs, 8-OHdG